Gustatory reaction time and time intensity measurements of trehalose and sucrose solutions and their mixtures - Galmarini, Mara Virginia (2009)
Fil: Galmarini, Mara Virginia. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina